2010
DOI: 10.1016/j.jcrs.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laser in situ keratomileusis in correcting anterior and non-anterior corneal astigmatism: Comparative study

Abstract: The efficacy of astigmatic correction by LASIK was significantly higher in eyes in which the preoperative refractive astigmatism was located mainly on the anterior corneal surface than in eyes in which it was mainly located posterior to the anterior corneal surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…It makes sense that, given the fact that the magnitude of the ORA seems to be similar in eyes with high myopic astigmatism than in those with low myopic astigmatism, then the ORA/ACA ratio would be higher in the latter group. This fact could explain why the preoperative ORA seems to play a significant role in the refractive outcome of eyes with low preoperative refractive astigmatism, 16,17 but seems to have a negligible effect in eyes with high preoperative astigmatism (as we found in the current paper).…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…It makes sense that, given the fact that the magnitude of the ORA seems to be similar in eyes with high myopic astigmatism than in those with low myopic astigmatism, then the ORA/ACA ratio would be higher in the latter group. This fact could explain why the preoperative ORA seems to play a significant role in the refractive outcome of eyes with low preoperative refractive astigmatism, 16,17 but seems to have a negligible effect in eyes with high preoperative astigmatism (as we found in the current paper).…”
Section: Resultssupporting
confidence: 64%
“…We also found that the visual and refractive results obtained after performing LASIK to correct high myopic astigmatism did not seem to be affected by the magnitude of the preoperative ORA. This seems to contradict the findings of Kugler et al 16 and Qian et al, 17 who studied the effectiveness of LASIK for correcting low myopic astigmatism and found significantly better refractive results in eyes with low ORA than in eyes with high ORA.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations